EFFICIENCY OF FINANCIAL RESOURCE MANAGEMENT AS A COMPONENT PART OF THE FINANCIAL POTENTIAL OF AN ENTERPRISE - Velykykh, K. (Municipal economy of cities. Series: «Economy science», 2023)
The article defines ways to increase the efficiency of financial resources management as a component of the financial potential of an enterprise. The algorithm proposed in the study for building a system for managing the financial resources of an enterprise is based on the processes of identifying a problem, analysing and finding ways to solve it, monitoring results, and determining prospects for adjusting management processes in the future, which allows not only to implement management mechanisms but also to carry out further control of their effectiveness and to introduce corrective influences into the system of managing financial resources at an enterprise. In the course of the study, we defined the concepts of financial resources and financial potential by analysing the theoretical approaches of various authors. Additionally, the author formulated a comprehensive definition of financial resource management. The article reviewed the groups of classifications of financial resources. Furthermore, the research determined methods for effective financial resource management, providing characterisations of each one from the point of view of the mechanisms of its practical implementation. The study culminated in establishing an algorithm for building a system for managing a company’s financial resources. It revealed the concepts of ‘financial potential’ and ‘financial resources’ to be interdependent and mutually complementary. As a result of the analysis, we concluded that the structure of financial resources consists of the sum of money within the analysed economic system. As an economic system for determining the processes of managing financial resources, you can choose both the level of individual households or subjects of economic activity (enterprises of various forms of ownership) and consider financial resources at the mesoeconomic and macroeconomic levels: municipalities, regions or territories, states, and international institutions. The article offers a systematic approach to defining the concept of financial resource management. Therefore, the management of financial resources is a system of management mechanisms used to implement the functions of planning, organisation, monitoring and control, and regulation of financial resources to ensure the strategic goals of developing a business entity and its competitive advantages in the market.